2021
DOI: 10.31234/osf.io/yajsk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Affective Film Dataset from India (AFDI): Creation and Validation with an Indian Sample

Abstract: We describe the creation of an affective film dataset for researchers interested in studying a broad spectrum of emotional experiences. Two hundred twenty-two 60-seconds long video clips were selected based on multimedia content analysis and screened in the lab with 407 participants. The participants' ratings mapped to 31 emotion categories in the first stage. Based on the selection criteria, 69 audio-visual clips were selected. These selected affective clips were then presented to 271 participants. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Although the probability of eliciting a particular category was not very high, we observed that the emotion labeling by participants during the EEG study generally matched with the top two labels reported in the dataset (the distribution of rated emotion categories by our participants is shown in Figure 4 ). We could think of the primary emotional category as target emotions, but our purpose was not to compare the emotional categories elicited in our study with those elicited in the video stimuli database [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the probability of eliciting a particular category was not very high, we observed that the emotion labeling by participants during the EEG study generally matched with the top two labels reported in the dataset (the distribution of rated emotion categories by our participants is shown in Figure 4 ). We could think of the primary emotional category as target emotions, but our purpose was not to compare the emotional categories elicited in our study with those elicited in the video stimuli database [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Before starting the main experiment, participants were trained using four emotional stimuli. The training stimuli were also taken from the same dataset, which we validated in an earlier study [ 35 ]. During the training, participants were informed about the experiment procedure, rating scales (given a quiz to assure they understood the self-assessment scales well), and trained to perform a mouse click when they felt any emotion and labeling these clicks with emotion categories.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli for emotion elicitation were selected from the affective stimuli dataset that we had developed (for stimuli [ 45 ]; for related article [ 46 ]). The following criteria were applied for the selection of stimuli: (1) high probability of emotion elicitation and good concordance score based on our earlier ratings study [ 45 ], (2) at least one stimulus from each emotion category, and (3) more preference to videos from India.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Stimuli for emotion elicitation were selected from the affective stimuli dataset that we had developed (for stimuli [43]; for related article [44]). The following criteria was applied for the stimuli selection: (1) High probability of emotion elicitation and good concordance score based on our earlier ratings study [43], (2) at least one stimulus from each emotion category, and (3) more preference to videos from India.…”
Section: Stimulimentioning
confidence: 99%
“…The following abbreviations are used in this manuscript: A1. Selected stimuli for EEG study from the stimuli dataset we have created (for stimuli [43]; for related article [44]). The time duration of each stimulus is 60 seconds.…”
Section: Institutional Review Board Statementmentioning
confidence: 99%